Mapping The Role and Collaboration of Stakeholders in Ecotourism Management and Creative Economic - Astriyantika, Meyliana; Cahyo, Enggar Dwi; Siregar , Damara Saputra (Jurnal Studi Perhotelan dan Pariwisata, 2024)
Purpose: This study aims to identify stakeholders in the development of Lugusari Tourism Village, Lampung, and map their roles to foster effective collaboration in preserving local culture, especially Lampung Tapis, and promoting a rural-based creative economy.Methodology: This research used a descriptive qualitative approach with data collection through field observations, interviews with stakeholders, and related literature studies. The data obtained was analyzed qualitatively to gain an in-depth understanding of the coordination flow and the role of each party in the management of Lugusari Tourism Village.Results: The results showed that the pentahelix model in tourism management is actively applied in Lugusari Tourism Village. The identified stakeholders include the government, private sector, academia, media, and the community. The coordination of tourism village management is centered on the village government, which acts as the main controller in terms of regulation, formulation of ideas and concepts, program implementation, and supervision of activities. Conclusions: It can be concluded that the successful management and development of Lugusari Tourism Village is highly dependent on the synergy between stakeholders through the pentahelix approach. Coordination centered on the village government allows for a structured development direction, but remains open to active contributions from various parties in developing authentic local potential.Limitations: This study is limited to Lugusari Village, so its findings may not be generalizable to other tourism villages in Lampung or Indonesia. Additionally, the methods used did not fully capture the dynamics of informal stakeholder relationships.Contributions: This research contributes to understanding the pentahelix model in developing tourism villages in Indonesia, especially in promoting sustainable, culture-based tourism and the creative economy. The findings can guide policymakers, tourism actors, and communities in creating inclusive, collaborative development strategies.Keywords: Creative Economy, Ecotourism, Lugusari Tourism village, Stakeholder Roles and CollaborationHow to Cite: Astriyantika, M, Cahyo, E, D, Siregar, D, S. (2024). Mapping The Role and Collaboration of Stakeholders in Ecotourism Management and Creative Economic. Jurnal studi perhotelan dan pariwisata, 3(1), 31-39.